2016
DOI: 10.1002/2016ja023171
|View full text |Cite
|
Sign up to set email alerts
|

GPS phase scintillation at high latitudes during the geomagnetic storm of 17–18 March 2015

Abstract: The geomagnetic storm of 17–18 March 2015 was caused by the impacts of a coronal mass ejection and a high‐speed plasma stream from a coronal hole. The high‐latitude ionosphere dynamics is studied using arrays of ground‐based instruments including GPS receivers, HF radars, ionosondes, riometers, and magnetometers. The phase scintillation index is computed for signals sampled at a rate of up to 100 Hz by specialized GPS scintillation receivers supplemented by the phase scintillation proxy index obtained from geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 55 publications
3
49
0
Order By: Relevance
“…We will therefore focus on this time period in the following and elaborate on the intense scintillation scenario of significant and coexisting amplitude and phase scintillations. The scintillation scenarios at other times during this storm are described by Jacobsen and Andalsvik () and Prikryl et al ().…”
Section: Observationmentioning
confidence: 92%
“…We will therefore focus on this time period in the following and elaborate on the intense scintillation scenario of significant and coexisting amplitude and phase scintillations. The scintillation scenarios at other times during this storm are described by Jacobsen and Andalsvik () and Prikryl et al ().…”
Section: Observationmentioning
confidence: 92%
“…The study of these irregularities is vital in understanding the signal observed at the ground; alternatively, the study of the signal as observed from the ground also plays an important role in understanding the formation and morphology of these irregularities. Attempting to relate the signal's features on the ground to the ionospheric phenomena which cause them has proven very useful in understanding the morphology and climatology of the ionosphere, with early works by Gruber () and Jespersen and Kamas (), and more recent works including Cervera and Thomas (), Beniguel et al (), Akala et al (), Paznukhov et al (), Mezaoui et al (), Prikryl et al (), and Prikryl et al () as examples. Several irregularity characteristics can be deduced by studying the rapid variations caused by the irregularities.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of works devoted to this problem (Aarons, 1997;Spogli et al, 2009;Shagimuratov et al, 2015a;Prikryl et al, 2015a;Cherniak and Zakherenkova, 2015;Prikryl et al, 2016). The occurrence of the scintillation at high latitudes is related to the patches in the auroral oval, cusp, and polar-cap.…”
Section: Introductionmentioning
confidence: 99%